Challenges of social service delivery to persons with disabilities in Egypt: A stakeholders' analysis - El Refaei, Amira Ayman (AUC Knowledge Fountain, 2016)
Social Rehabilitation Offices are one of the most vital outlets in Egypt that provide services to persons with disabilities (PWDs) under the supervision of the Ministry of Social Solidarity (MoSS). This study seeks to document the performance of Social Rehabilitation Offices from a multi-dimensional perspective; persons with disabilities (beneficiaries), Rehabilitation Offices (service providers), partner non-governmental organizations (NGOs) working in the field of disability, and MoSS (regulators). A mixed methods approach was used to gain an in-depth perspective to the complexity of the issues present in the Egyptian social service delivery system. It was clear that not all Rehabilitation Offices are performing with the same quality, efficiency and effectiveness. The service providers and regulators hold more positive views towards the services provided by the offices than beneficiaries. PWDs are not able to exercise their full rights as a result of receiving little information about the services. More effort can be done regarding the training and employment of PWDs. Also, the study shows lack of clarity of roles and responsibilities for several stakeholders, which had an impact on the quality of services provided. Structural issues such as lack of coordination among multiple stakeholders, poor financial support, a weak monitoring system, and weak social support to PWDs were also found to negatively impact the quality of services. Recommendations for enhancing the performance of these Rehabilitation Offices and the overarching system are listed.